STUDI KONTRASTIF KONSTRUKSI INTEROGATIF POLAR BAHASA JEPANG DAN BAHASA INDONESIA - Abdul Gapur; Mulyadi Mulyadi (GENTA BAHTERA: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
This research discusses about interrogative construction of polar in Japanese and Indonesian language. The purpose of this research describes the forms, similarities and differences, and the correspondence of interogative constructions in Indonesian and Japanese. Sources of data are related literature on interrogative constructions and Indonesian and Japanese grammar books. Data collection using techniques of refering and noting.Contrastive analysis is used to analyze data. The he study found that the interrogative contrastive polar in Japanese and Indonesian languages were formed from use of 1) intonation, 2) interrogative particles, and 3) interrogative tags. The interrogative constructions of Japanese and Indonesian polar interrelations are inherent in the intonation aspect as the main thing in the construction of polar interrogation, the use of interrogative particles and the use of nterogative tags in both languages. The difference between polar interrogative constructions lies in the use of more productive ”apa”, “apakah”  and “bagaimana” words in Indonesian and more productive interrogative particles in Japanese polar interrogative. In the correspondence of translations most of the interrogative particles of Japanese are equated with the question 'apakah' in the polar interrogative constructions of Indonesian. AbstrakPenelitian ini membahas tentang konstruksi interogatif polar dalam bahasa Jepang dan bahasa Indonesia. Tujuan penelitian ini untuk mendeskripsikan bentuk, persamaan dan perbedaan, dan kesepadanan konstruksi interogatif dalam bahasa Indonesia dan bahasa Jepang. Sumber data adalah literatur yang berkaitan tentang konstruksi interogatif dan buku tatabahasa Indonesia dan bahasa Jepang. Pengumpulan data dengan teknik catat. Analisis data menggunakan analisis kontrastif dengan pendekatan strukturalis. Hasil penelitian ditemukan bahwa kontrastif interogatif polar bahasa Jepang dan bahasa Indonesia terbentuk dari 1) penggunaan intonasi, 2) partikel interogatif, dan 3) tag interogatif. Persamaan bentuk konstruksi interogatif polar bahasa Jepang dan Indonesia terdapat pada aspek intonasi sebagai hal utama dalam pembentukan konstruksi interogatif polar, penggunaan partikel interogatif dan penggunaan tag Interogatif dalam kedua bahasa. Perbedaan konstruksi interogatif polar terletak pada penggunaan kata tanya ”apa”, “apakah” dan “bagaimana” yang lebih produktif dalam bahasa Indonesia dan partikel interogatif ka yang lebih produktif sebagai penanda interogatif polar dalam bahasa Jepang. Dalam kesepadanan penerjemahan umumnya partikel interogatif ka bahasa Jepang disepadankan dengan kata tanya ”apakah” dalam konstruksi interogatif polar bahasa Indonesia.